Ten things your EII vendor may not tell you the hidden complexities of implementing an EII solution. - Luu, Tieu
Enterprise information integration (EII) is getting a lot of hype these days, and the vendors are giving you very compelling reasons for why you need an enterprise data access layer based on their EII product. However, a lot of the scenarios and case studies they present are very targeted or are simple examples of how their product works that don't delve into the complexities of a real-world environment. This article presents some of those complexities and demonstrates how some of the EII products may not provide adequate functionality for an environment with such complexities.